Relocation, Climate Change and Finding a Place of Belonging for Rohingya Refugees. Issue 3 (December 2022) - Shahpur, Tengku; Wardani, Abellia Anggi
An estimated 745, 000 Rohingyas were forced to flee to Cox's Bazar, Bangladesh, after a deadly crackdown in Rakhine state, Myanmar in August 2017. Responding to this crisis, the Bangladesh government launched the relocation of Rohingyas from the dense camps in Cox's Bazar to Bhasan Char island in the Bay of Bengal in December 2020. This article argues that the refugees' perceptions of their idealized "home"—their place of belonging—composed of complex needs with security tied to environmental stability, have not adequately been considered in their relocation to Bhasan Char island. Further, the physical threats of climate change on the island combine with a denial of the spatial and cultural dimensions of home, creating the threat of Rohingyas becoming "recycled refugees." The findings are based on qualitative case study research conducted with Rohingya refugees residing in Cox's Bazar and with those recently relocated to Bhasan Char.